Analysis of 10 years (2007 - 2016) of epidemiological data of urinary stones in dogs and cats from a referral centre in Malaysia - Tajudeen, Hameedunisha (2017)
Urolithiasis a common urinary problem in dogs and cats. The objective of this study was to evaluate epidemiological data derived from a referral center in Malaysia over 10 years (2007 – 2016). Urolith analysis results of dogs and catspertaining to their respective urolith type and composition, were evaluated and compared with breed, age, sex, neuter status, body condition score, urine pH and anatomical location. Out of 1086 uroliths analyzed, 90.4% were from dogs and 9.6% from cats. Majority of uroliths from dogs and cats (89.8% and 92.2%, respectively) were from the lower urinary tract. Struvite (61.1%) was most commonly found in dogs and calcium oxalate (CaOx) (51.9%) in cats. The average age of dogs and cats were 5.8 years for struvite and 7.6 years for CaOx. Dogs were 2.7x more likely to develop struvite than cats and cats were 2.4x more likely to develop CaOx than dogs. Bitches were 11.9x more likely to develop struvite than males. Meanwhile, toms were 1.5x more likely to develop CaOx than queens.Most common dog and cat breeds associated with struvite and CaOx were Shih Tzu, mixed-breed dogs, Miniature Schnauzers, Domestic Shorthair, Persians and mixed-breed cats. This is the first epidemiological study of uroliths in Malaysia, with significant differences in urolith occurrence between dogs and cats. This baseline data can be useful for further investigative studies towards species specific management of urolithiasis.